2016
DOI: 10.1167/iovs.15-18530
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Outcomes Comparison Between 14- and 70-Day Head-Down-Tilt Bed Rest

Abstract: PurposeTo compare ocular outcomes in healthy subjects undergoing 14- and/or 70-day head-down-tilt (HDT) bed rest (BR).MethodsParticipants were selected by using NASA standard screening procedures. Standardized NASA BR conditions were implemented. Subjects maintained a 6° HDT position for 14 and/or 70 consecutive days. Weekly ophthalmologic examinations were performed in the sitting (pre/post-BR only) and HDT positions. Mixed-effects linear models compared pre- and post-HDT BR observations between 14- and 70-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 22 publications
3
53
0
1
Order By: Relevance
“…Studies of fluid shifts in relation to cardiovascular and ocular examination during long-duration spaceflight are currently underway with ISS astronauts. Ophthalmic issues have been assessed in head-down tilt (HDT) bed rest, an often used analog of weightlessness, with some subclinical findings but none as overt as those observed after actual spaceflight (3,(58)(59)(60). Diuresis occurs in HDT bed rest but not during spaceflight, and total body water decreases during HDT bed rest but is unchanged during spaceflight (56).…”
Section: Variations In Genetics Of Enzymes In the 1-carbon Metabolic mentioning
confidence: 99%
“…Studies of fluid shifts in relation to cardiovascular and ocular examination during long-duration spaceflight are currently underway with ISS astronauts. Ophthalmic issues have been assessed in head-down tilt (HDT) bed rest, an often used analog of weightlessness, with some subclinical findings but none as overt as those observed after actual spaceflight (3,(58)(59)(60). Diuresis occurs in HDT bed rest but not during spaceflight, and total body water decreases during HDT bed rest but is unchanged during spaceflight (56).…”
Section: Variations In Genetics Of Enzymes In the 1-carbon Metabolic mentioning
confidence: 99%
“…5 Ocular effects during bed rest are now being studied more systematically, with a recent investigation showing that a 70-day bed rest induced greater peripapillary retinal thickening than a 14-day bed rest. 6 The present study was part of a larger research program investigating the effect of the anticipated environments in future planetary habitats, 7 which will be hypobaric and hypoxic, on physiological systems. The purpose of establishing a hypobaric hypoxic environment in space habitats is primarily to eliminate the need for long decompression profiles requiring oxygen breathing prior to extravehicular activities.…”
mentioning
confidence: 99%
“…25, 29 Proposed mechanisms to explain the IOP elevation during head-down-tilt include increased episcleral venous pressure and choroidal engorgement with expansion against the sclera, respectively. 4, 15 In our study, we found no differences in iCare IOP elevation between controls and exercisers (+1.38 mmHg and +1.63 mmHg increase from baseline, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Mixed-effect restricted maximum likelihood regression models have recently shown the importance of the time spent in head-down-tilt on the magnitude of peripapillary thickness changes induced by bed rest. 29 Thus, it is expected that longer bed rest durations would result in greater cpRNFL thickening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation